In-situ investigation of quenching and partitioning by High Energy X-Ray Diffraction experiments. (1st April 2017) - Allain, S.Y.P.; Geandier, G.; Hell, J.C.; Soler, M.; Danoix, F.; Gouné, M.
Abstract: We report the first ultra-fast time-resolved quantitative information on the quenching and partitioning process of conventional high strength steel by in-situ High Energy X-Ray Diffraction experiment. The time and temperature evolutions of phase fractions, their carbon content and internal stresses were determined. The austenite to martensite transformation below Ms is followed by a stagnant stage during which microstructural state remained unchanged. Afterwards, a fast kinetics of carbon enrichment of austenite during the partitioning step at 400 °C is highlighted. The analysis proposed supports the carbon diffusion from martensite to austenite as the main mechanisms responsible for this enrichment. Graphical abstract: